2013
DOI: 10.1002/hyp.9665
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based regularization of the extracted topographic index from high-resolution topography for hydro-geomorphic applications

Abstract: High‐resolution topography, e.g. 1‐m digital elevation model (DEM) from light detection and ranging (LiDAR), offers opportunity for accurate identification of topographic features of relevance for hydrologic and geomorphologic modelling. Yet, the computation of some derived topographic properties, such as the topographic index (TI), is characterized by daunting challenges that hamper the full exploration of topography‐based models. Particular problems, for example, arise when a distributed (or semi‐distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Digital Elevation Model for the watersheds was interpolated to 25 m grid based on LiDAR data. The grid size was this is a compromise between using a lower resolution that causes a loss of information about hillslope flow pathways, and a high resolution that is influenced by noise (Nourani and Zanardo 2014). Based on the flow accumulation maps generated using GIS tools, the TWI value was assigned to each raster cell in the digital elevation models of the watersheds.…”
Section: Terrain Characteristicsmentioning
confidence: 99%
“…Digital Elevation Model for the watersheds was interpolated to 25 m grid based on LiDAR data. The grid size was this is a compromise between using a lower resolution that causes a loss of information about hillslope flow pathways, and a high resolution that is influenced by noise (Nourani and Zanardo 2014). Based on the flow accumulation maps generated using GIS tools, the TWI value was assigned to each raster cell in the digital elevation models of the watersheds.…”
Section: Terrain Characteristicsmentioning
confidence: 99%
“…Therefore for both daily and monthly data of two case studies (the Delaney Creek and Payn selected sub-series via four feature extraction criteria (i.e., H, MI, E and CC). In order to survey the performance of H, CC, E and MI feature extraction criteria, for instance in daily data, the sub-series of the first, second and third ranks (according to the Table 4) were primarily considered as the inputs of FFNN; thereinafter, the sufficient number of inputs was consequently determined using the maximum reduction rate method proposed by Nourani and Zanardo (2014). Table 5 presents the results of developed FFNN models using the selected sub-series decomposed by Haar, db2 and db4 mother wavelets for daily data.…”
Section: Results Of Ewann Modelmentioning
confidence: 99%
“…As a research plan and due to social and economic importance of the study areas, it is suggested to couple the proposed ANN-based model to a geomorphology-based rainfall-runoff model (e.g., TOPMODEL, Nourani and Zanardo, 2014) to have a comprehensive semi-distributed rainfall-runoff modeling for the site.…”
Section: Discussionmentioning
confidence: 99%
“…Topographical factors have an important influence on the spatial distribution of cultivated land elements. A single elevation or slope does not accurately reflect the degree of impact [48]. Therefore, this paper introduces the topographical position index (comprehensive calculation of elevation and slope) to characterize the spatial distribution characteristics of cultivated land.…”
Section: Topographic Position Indexmentioning
confidence: 99%